(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This thesis explores the profound impact of linguistic diversity and globalization on our interconnected world, shedding light on the transformative potential of multilingual education. With thousands of languages spoken across the globe, our planet is a vibrant tapestry of cultures and traditions. Simultaneously, globalization has intricately linked societies, businesses, and communication networks, necessitating a skill set that transcends borders. Multilingualism, once considered an asset, has now evolved into a valuable skill in the global job market. It serves as a bridge between cultures, enabling effective cross-cultural communication and unlocking a world of opportunities